Evaluation of aerobic bacterial normal flora of conjunctiva in healthy persons, Babol Shahid Beheshti Hospital - A Soleimani (Babol University of Medical Sciences, 2003)
Background and Objective: Conjunctiva is a mucusal surface colonized by a bacterial microflora that seems to be involved in some eye infections such as conjunctivitis, keratitis and endophtalmitis after ocular trauma, surgery or other causal condition. So it is essential to know the normal flora composition. The aim of this study was to know what the normal aerobic bacterial conjunctival flora is. So when the infection occurs, we can choose the antibacterial drugs, before culture and antibiogram. Methods: This experimental study was performed on 135 healthy persons without conjunctivitis who referred to the eye clinic of Shahid Beheshti hospital of Babol during 2001. Swab specimens were collected from both eyes of every case (Without use of tetracaine), and cultured on blood-agar (5%) and then medium and finally diagnostic bacteriologic studies and essential differential tests were performed on them. Findings: Among 135 studied cases, 70 were male and 65 were female. The youngest one was 1 year old and the oldest 70 years. Of 270 swab specimens, growth was in only 27.7% (n=75) of cases. Also, 41% of healthy persons had normal conjunctival aerobic bacteria. The colonization happened to be unilateral in 67% (n=37) and bilateral in 33% (n=19) of cases. Also, among 75 studied colonies, 84% (n=63) was monobacterial and 16% (n=12) was polybacterial. There were 43 positive cultures of coagulase-negative staphylococci, 11 non-pathogenic neisseria, 10 gram-negative bacilli, 7 coagulase-positive staphylococci and 4 positive cultures of gram-positive bacilli. Conclusion: Conjunctival colonization with aerobic bacteria accounts for approximately 50% of healthy people that mostly occur unilateral and consists of predominantly one aerobic bacterial species. Coagulase-negative staphylococci are the main components of this flora.